Mobile Game-Based Learning (mGBL): Application Development and Heuristics Evaluation Strategy (Malaysian Journal of Learning and Instruction, 2010)
Purpose â€“ This article presents an approach to developing a mobile game-based learning (mGBL) application by adapting unified characteristics of learning theories and approaches. In addition, the study also identified the strategy to evaluate mGBL. Method â€“ The study utilized the design research approach in information systems. The research methodology can be divided into five phases; (i) awareness of problem (ii) suggestion (iii) development (iv) evaluation and (v) conclusion. Findings â€“ Unified characteristics of mGBL were identified. In adapting the characteristics, the mGBL application was developed based on the concept of values in 1Malaysia. To evaluate the mGBL, a heuristics evaluation strategy is proposed. The strategy consists of four components: Game Usability, Mobility, Game Play, and Learning Content. Each of the components represents the issues to be considered and evaluated for a mGBL. Value â€“ The study provides intensive review of mGBL characteristics that can be useful and may be of interest to game developers. In addition the heuristics evaluation strategy is developed for evaluating the effectiveness of mGBL application.